Perlindungan Hukum Terhadap Pasien Dalam Pelayanan Medis Di Rumah Sakit Umum (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
Medical services are the object of forgiveness for treatment and care. So efforts to improve people's living standards in the health sector, is a comprehensive necessity including improving public health physically and non-physically. In this case, the patient is someone who receives medical treatment. The patient's right as a recipient of medical services is to obtain information on medical services to find out the results of the examination/diagnosis that has been carried out by the medical team and the right to know what action the patient must receive.